Phenotypic and genetic relationships between docility and reproduction in Angus heifers - Otteman, Kari Lynn (Kansas State University, 2013)
This thesis includes two studies that assessed the relationships between docility and reproduction in Angus heifers, both from a phenotypic and genetic standpoint. The objective of the first study was to elucidate the phenotypic relationships between docility and first service AI conception rate in heifers. Data (n = 337) included exit velocity (EV), chute score (CS), fecal cortisol (FC), and blood serum cortisol (BC). Statistical analysis was done using logistic regression with 30 day pregnancy rate as the dependent variable. The model included the fixed effect of contemporary group, and the covariates FC, BC, EV, CS, weight, and age. Correlation coefficients were also calculated between all continuous traits. The power of our test could not detect any significant predictors of 30 d pregnancy for the combined data from all ranches. The objective of the second study was to determine the genetic control of docility and reproduction in heifers as measured by pregnancy rate. A subjective chute scoring system was used as the basis of their genetic evaluation for docility. Pedigree information was obtained on approximately 508,015 animals over 30 generations. Data included approximately 26,878 records on heifer pregnancy and 113,412 records on docility, with 7,849 animals having both docility and heifer pregnancy records. Contemporary groups were formed by the concatenation of weaning contemporary group, yearling contemporary group, and breeding contemporary group. Heritabilities were calculated from estimates of genetic and residual variance components computed using ASReml 3.0 (VSN International; Hemel Hempstead, UK). Heifer pregnancy variance components were estimated from a univariate, threshold model, with pregnancy outcome as the dependent variable. Animal and contemporary group were fit as a random effects, while age at first breeding was fit as a covariate. The heritability of heifer pregnancy was estimated to be 0.16 ± 0.02. Docility was fit as a univariate, linear animal model with docility score as the dependent variable. Animal and contemporary group were both modeled as random effects. The heritability for docility score was estimated to be 0.22 ± 0.03. Fertility is a complex trait that is dependent on many factors; our data suggest that docility is one factor that warrants further investigation.
Keywords: Beef cattle; Genetic parameters; Docility; Reproduction; Animal Sciences (0475)